Obesity and menopause - Albert A. Opoku FRCOG (15955340) (2023)
The global obesity pandemic continues to rise, with figures from the World Health Organization showing that 13% of the world's adult population was obese in 2016. Obesity has significant implications, with an increased risk of cardiovascular diseases, diabetes mellitus, metabolic syndrome, and several malignancies. The menopausal transition is associated with increased obesity, a transition from a gynecoid to an android body shape, and increased abdominal and visceral fat, which further worsens the associated cardiometabolic risks. Whether this increased obesity is a consequence of menopause, age, genetics, or environmental factors has long been debated. Increasing life expectancy means women spend a significant part of their lives in the menopause. As such, understanding this complex interplay of obesity and menopause is important to providing the right advice/management. We review the current evidence on obesity and menopause, focusing on the implications of increased obesity during menopause, the impact of menopause on obesity, and the effect of available treatments on associated morbidities. Other Information Published in: Best Practice & Research Clinical Obstetrics & Gynaecology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://doi.org/10.1016/j.bpobgyn.2023.102348